Islam’s View of Religion and State: A An Overview - Andi Eliyah Humairah; Darussalam Syamsuddin (JIA (Jurnal Ilmu Agama), 2024)
Discussions about the relationship between religion and the state always occur in a stigmatic atmosphere. This is because first, the relationship between religion and state in Islam is the most impressive thing in human history. Second, throughout history, the relationship between Muslims and non-Muslims (European Christians) has been a relationship full of tension. This article examines the relationship between religion and the state from an Islamic perspective. By using qualitative methods and descriptive-analytical data analysis techniques, this article concludes that firstly, religion is a statute or law that must be obeyed by humans, while the state in the Islamic perspective is an area of ​​power that has territorial boundaries, in In this area there are groups, religious human associations, there are rulers, there is justice and a safe atmosphere is created, the soil is fertile, and there are future generations. Second, the problem of the relationship between religion and the state has emerged in a series of polemics and debates that have occurred in the Islamic world. One of these debates occurred during the Turkish revolution under the leadership of Mustafa Kemal in 1924, which resulted in the abolition of the caliphate in al-Khulafa’ al-Rasyidun, namely the title for the four caliphs who led after the Prophet Muhammad died. In understanding the relationship between religion and the state, there are several concepts of the relationship between religion and the state according to several schools/understandings, including: theocracy, secondary ideology, and communist ideology.